2002
DOI: 10.5694/j.1326-5377.2002.tb04516.x
|View full text |Cite
|
Sign up to set email alerts
|

End‐stage renal disease in the Northern Territory: current and future treatment costs

Abstract: Objective:To compare hospital costs of Aboriginal and non-Aboriginal patients having haemodialysis treatment and forecast the future treatment cost. Methods:The costs of patients with HD in the "Top End" of Australia's Northern Territory were estimated for the financial years 1996/97 and 1997/98 using a hospital costing model. We used an Autoregression Integrated Moving Average model to predict future demand.Results: 165 patients (101 Aboriginal and 64 non-Aboriginal) were treated at a total cost of $12.4 mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…One early task was the description of the rise of ‘RRT’ in all of the remote Aboriginal settings in NT and documentation of its great costs [3, 8, 9]. The application of quantitative tests for proteinuria (superseded by the urinary albumin/creatinine ratio, ACR), and creatinine-based estimates of glomerular filtration rate (eGFR), ushered in studies of the underlying renal disease.…”
Section: Recent Findings and Eventsmentioning
confidence: 99%
“…One early task was the description of the rise of ‘RRT’ in all of the remote Aboriginal settings in NT and documentation of its great costs [3, 8, 9]. The application of quantitative tests for proteinuria (superseded by the urinary albumin/creatinine ratio, ACR), and creatinine-based estimates of glomerular filtration rate (eGFR), ushered in studies of the underlying renal disease.…”
Section: Recent Findings and Eventsmentioning
confidence: 99%
“…While our knowledge of the true economic impact of ARF/RHD remains limited, this is nonetheless extremely good value for money compared with other health interventions in this and other settings. For example, one study in the Northern Territory found that the average annual cost of providing dialysis and other treatment to Aborigines with end‐stage kidney disease was at least $71 000 …”
Section: The Screening Programmentioning
confidence: 99%
“…Transplant rates for Aboriginal people from the NT are 10% lower than the national average. The contributing factors include the low number of indigenous organ donations, distance from the transplanting hospital in Adelaide, and the ability to complete the work‐up for transplant 2 . From January 1997 to December 2001, there were four Aboriginal organ donors in Australia, compared with 927 non‐Aboriginal people 3 .…”
Section: Why Pursue Indigenous Organ Donation?mentioning
confidence: 99%